CD56 in the Immune System: More Than a Marker for Cytotoxicity? - Van Acker, Heleen H.; Capsomidis, Anna; Smits, Evelien L.; Van Tendeloo, Viggo F. (Frontiers in Immunology, 2017)
Over the past years, the phenotypic and functional boundaries distinguishing the main cell subsets of the immune system have become increasingly blurred. In this respect, CD56 (also known as NCAM) is a very good example. CD56 is the archetypal phenotypic marker of natural killers cells, but can actually be expressed by many more immune cells, including alpha beta (αβ) T cells, gamma delta (γδ) T cells, dendritic cells and monocytes. Common to all these CD56-expressing cell types are strong immunostimulatory effector functions, including T helper 1 cytokine production and an efficient cytotoxic capacity. Interestingly, both numerical and functional deficiencies and phenotypic alterations of the CD56+ immune cell fraction have been reported in patients with various infectious, autoimmune or malignant diseases. In this review, we will discuss our current knowledge on the expression and function of CD56 in the hematopoietic system, both in health and disease.